Pengaruh Tax Minimization, Tunneling Incentive Terhadap Transfer Pricing Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Wahyu Nurul Hidayati; Nabila Alfi Sylvatica; Aris Sanulika (Universitas Pamulang, 2020)
This study aims to find out the influence of tax minimization and tunnelling incentives on transfer pricing with the size of the company as a moderation variable. Independent variables used are tax minimization and tunnelling incentive, while dependent variables used are transfer pricing and for moderation, variables are the size of the company. The sample of this study was a Food and Beverage Sub-Sector Manufacturing Company listed on the Indonesia Stock Exchange that presented its financial statements from 2015 to 2019 with the number of samples in this study as many as 10 companies. The method of determining samples in this study uses purposive sampling, while the data processing method in this study uses a statistical package for the social science (SPSS) version 25. The results of this study showed that the variable tax minimization has no effect on transfer pricing, tunnelling incentive variable has an influence on transfer pricing, then the tax minimization variable with the moderation of company size strengthens the effect on transfer pricing and the tunnelling incentive variable with moderating company size weakens the effect on transfer pricing. Keywords: Tax Minimization; Tunneling Incentive; and Company Size; Transfer pricing.